Primary pizzazz writing - Forney, Melissa (Gainesville, Fla Maupin House Pub, 2005)
Want to teach to the K-2 writing standards, get ideas galore, and have fun with your primary writing workshop, too? Of course. You want it all. And now you can have it! Primary Pizzazz Writing really helps you do it all! Create a successful craft-centered writing workshop classroom. Directly address all of the nationally recognized primary writing standards with 30 Skill Units for every teaching setting large and
a gift from book africa
1 2 13 15
Keywords: English language -- Composition and exercises -- Study and teaching (Primary); Language arts (Primary)